1997
DOI: 10.1029/97jd01690
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet optical model of volcanic clouds for remote sensing of ash and sulfur dioxide

Abstract: Abstract. The total ozone mapping spectrometer (TOMS) instruments have detected every significant volcanic eruption from November 1978 to December 1994 on the Nimbus 7 and Meteor 3 satellites and since July 1996 on the new satellites, TOMS-Earth Probe and ADEOS. We apply a radiative transfer model to simulate the albedos of these fresh eruption clouds to study the limitations of the present algorithm which assumes an absorbing cloud above a scattering atmosphere. The conditions are found to be approximated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…The SO 2 retrieval is based on the Residual Model of Krueger (1983) which was later replaced by the Linear Model (Kerr Algorithm) (Kerr et al, 1980;Krotkov et al, 1997;Krueger et al, 2000). The Linear Model assumes that solar radiation is attenuated by absorbing species according to Beers law so that:…”
Section: Tomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SO 2 retrieval is based on the Residual Model of Krueger (1983) which was later replaced by the Linear Model (Kerr Algorithm) (Kerr et al, 1980;Krotkov et al, 1997;Krueger et al, 2000). The Linear Model assumes that solar radiation is attenuated by absorbing species according to Beers law so that:…”
Section: Tomsmentioning
confidence: 99%
“…TOMS detects backscattered radiation in the near-ultraviolet region of the electromagnetic-spectrum and measures in six wavelength bands from 308 nm to 360 nm (Krotkov et al, 1997). A Sulphur Dioxide Index (SOI) is computed to indicate the presence or absence of SO 2 by comparison with pre calculated radiances (Bhartia, 2003;McPeters et al, 1998).…”
Section: Tomsmentioning
confidence: 99%
“…[28] Krotkov et al [1997] suggest that TOMS SO 2 can be overestimated by 15-25% when significant ash is present in the SO 2 cloud. Guo et al (submitted manuscript, 2004) concluded that ash fell out very rapidly, so this overestimate would be expected to be strongest on the first day.…”
Section: Total So 2 Mass Increase After Eruptionmentioning
confidence: 99%
“…Despite their irregular shape, ash particles are most commonly modeled as spheres in both transport modeling experiments [ Brazier et al , 1982; Carey and Sigurdsson , 1982; Suzuki , 1983; Armienti et al , 1988; Glaze and Self , 1991; Sparks et al , 1992; Jarzemba et al , 1997] and remote sensing algorithms [ Wen and Rose , 1994; Krotkov et al , 1997] primarily because no quantitative description of particle shape has been made. Numerous qualitative SEM studies (summarized by Heiken and Wohletz [1985]) have shown that volcanic particles are generally quite angular and/or irregular and include parachute‐shaped bubble wall shards, equant mineral grains, and subrounded vesicular pumice clasts (Figure 1).…”
Section: Introductionmentioning
confidence: 99%